Prevalent Pest Management Strategies for Grain Aphids: Opportunities and Challenges - Luo, Kun; Zhao, Huiyan; Wang, Xiukang; Kang, Zhensheng (Frontiers in Plant Science, 2022)
Cereal plants in natural ecological systems are often either sequentially or simultaneously attacked by different species of aphids, which significantly decreases the quality and quantity of harvested grains. The severity of the damage is potentially aggravated by microbes associated with those aphids or the coexistence of other fungal pathogens. In agricultural production, grain aphid control depends greatly on chemical spraying, and the use of cultivars with single-gene based antibiosis resistance has accelerated the evolution of insecticide resistance and a resultant pest resurgence. It is important that effective and environmentally friendly pest management measures to control the damage from grain aphids on cereals in agricultural ecosystems be discovered. In recent decades, extensive studies have typically focused on further understanding the relationship between crops and aphids, which has greatly contributed to the establishment of sustainable pest management approaches. This review discusses recent advances related to the control of grain aphids. The current and expanding knowledge shows that the large-scale cultivation of aphid-resistant wheat cultivars integrated with agricultural and/or other management practices will be the most prevalent and economically important management strategy for wheat aphid control.